The Application of “Blended Learning-Rigorous Mathematical Thinking” Model to Improve Students’ Spatial Thinking Ability - Makmun Hidayat; Mustadji Mustadji; Bachtiar Saiful Bachri; Bakhrul Khair Amal (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is a quantitative descriptive study that explains the improvement of students' spatial thinking skills after the implementation of the blended learning-rigorous mathematical thinking model, hereinafter referred to as the BL-RMT model. Spatial thinking ability (KBSp) which is measured in this study is related to the mathematics subject in the aspect of geometry. The design of this study used a "Control Group Pretest-Postest Design" with the research sample being class VIII students at Madrasah Tsanawiyah Negeri 2 Sidoarjo. Data collection uses a test technique with an instrument in the form of questions. Data analysis using normalized Gain test (N-Gain Test) andThe t-test was performed using SPSS Independent samples test. The results showed that in the experimental class the mean value of the KBSp pre test is 68.5593 dan the average test post is 83.5593. Tthere is an increase in the average value of 15 digits and if calculated based on the N-Gain formula, a score of 0.477 is obtained in the medium Gain category. While in the control class, the mean of pre-test KBSp was 67.2581 and the mean of post-test was 75.5161. There isan increase in the average value of 8.258 and if calculated based on the N-gain formula, a score of 0.252 is obtained in the low category. Furthermore, based on the results of the t-test on the KBSp pre-test value, the result was 0.375 with a Sig (2-tailed) value of 0.708 > 0.05 ortcount < t table for = 0.05, meaning that there is no difference between the pre-test scores of the experimental class and the control class or the two groups are homogeneous.